2018
DOI: 10.1186/s12885-018-4424-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous renal hemorrhage secondary to choriocarcinoma in a man with congenital hypospadias and cryptorchidism: a case report and literature review

Abstract: BackgroundChoriocarcinoma is a rare malignant germ-cell tumour, most commonly found in adult women. It infrequently presents as spontaneous renal haemorrhage (SRH). Genital malformation and SRH secondary to choriocarcinoma has previously been only reported in females. We present what we believe to be the first case of a male patient with genital malformation (hypospadias and cryptorchidism) and SRH at presentation of choriocarcinoma.Case presentationA 25-year-old man presented to the department with intense pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a similar case, Li et al. ( 9 ) used the open surgical approach and partial nephrectomy to control the bleeding. In the cases of Vijay et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar case, Li et al. ( 9 ) used the open surgical approach and partial nephrectomy to control the bleeding. In the cases of Vijay et al.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous nontraumatic renal hemorrhage was rst documented in the literature by Bonet in 1700 as a rare disease, although it was again reported as Wünderlich syndrome by a German doctor in 1856. [1][2][3][4][5][6][7][8][9][10][11][12][13] Spontaneous bilateral renal hemorrhage is extremely rare because it is unlikely to occur in the absence of anticoagulant or antiplatelet intake when it occurred consecutively not simultaneously. 14 In our case, the rst event of the renal hemorrhage occurred when the patient took clopidogrel (oral antiplatelet) daily, and the second event of renal hemorrhage occurred only 15 days after the rst hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases were caused by vascular proliferative tumors, such as renal cell carcinoma or angiomyolipoma (57-73%) or choriocarcinoma, followed by autoimmune vasculitis including polyarteritis nodosa (PAN) or segmental arterial mediolysis. [1][2][3][4][5][6][7] In particular, spontaneous bilateral renal hemorrhages accounted for only 3% of all case reports on spontaneous renal hemorrhage, and all cases were PAN. 14 Phillips et al reported that BehÇet's disease and segmental arterial mediolysis may cause spontaneous renal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported the case of a 25-year-old man who presented with spontaneous renal hemorrhage, which on further workup was found to be secondary to choriocarcinoma; however, the case was complicated by cryptorchidism and hypospadias. 3 The authors suggested choriocarcinoma was a difficult diagnosis because of its unusual presentation. We report on the second patient to be found with this presentation, who also had widespread disease with metastases in the lungs, mediastinal lymphnodes, and lower pole of the right kidney.…”
Section: Discussionmentioning
confidence: 99%